Problems in the Protection of the Modem Architectural Heritage in Turkey: Case Study - Sisli Liquor Factory in Istanbul - Sazak, Saduman; Kiran, Hatice (CHANDIGARH COLL ARCHITECTURE, 2014)
Beginning with the twentieth century, architectural heritage is mostly understood the need to protect and successfully protected the number of samples has been increasing with each passing day. Unfortunately, today, there are some problems for the conservation of modern architectural heritage in some European countries which were the leader on conservation issues, About the preservation of modern architecture in Turkey is experiencing serious problems. Of today's modern architectural production in Turkey unhealthy urbanization role in shaping our cities leads to perceived negatively by society. On the one hand associated with protection in this direction, the negative social perception as well as the current legal regulations (laws) on this topic restrictive provisions, to protect the public consciousness, the lack of organizational shortcomings and ignorance the other hand, the current economic approach is done to protect the environment rather than being converted (urban renewal) due to choose, the twentieth century structures that can be removed easily overlooked in the process of regeneration is caused. In this study, the twenty-first century problems at the protection of the twentieth century modern architectural heritage in Turkey will be discussed and an industrial heritage; Sisli Liquor Factory, Turkey's first concrete technique applied, as a case example, will be evaluated.
Keywords: conservation; modern architecture; sisli liquor factory; turkey; Architecture